EFFECTIVENESS OF THE SCHOOLS’ INTERNAL AUDITORS IN PERAK - Mahajar, Abdul Jumaat; Yunus, Jasmani Mohd; Yusof, Hasmida; Yeop Yunos, Nek Kamal (International Business Education Journal, 2011)
The research was carried out in January 2009. The study was to identify the important elements in the effectiveness of the internal auditors of primary and secondary schools in Perak. Factors were examined for the effectiveness of school internal auditor.They were experience,knowledge and skill,management support and organization setting. There are 100 respondents responded to the questionnaires. They were amongst the internal school auditors in Perak. A pre-test was carried out for the study. This study used frequencies,Pearson correlation and multiple regressions. It was found out that there were two main important factors that contributed to the effectiveness of the school internal auditors. They were such as management support and organization setting. This study proposed that in order to increase the effectiveness of the school internal auditors, the teacher’s work load should be reduced and the teachers must be continually encouraged to attend seminar and courses in auditing.